Association between erythrocyte membrane fatty acids and gut bacteria in obesity-related cognitive dysfunction - Tong Zhao; Hongying Huang; Jinchen Li; Jingyi Shen; Cui Zhou; Rong Xiao; Weiwei Ma (AMB Express, 2023)
Abstract Obesity increases the risk of cognitive impairment and dementia, and the gut microbiota can affect brain cognitive function and obesity through a variety of pathways such as the gut-brain axis. This study aimed to discover how fatty acid affect cognitive function by regulating intestinal flora in obesity. Obese subjects were recruited for cognitive function assessment, and participants were divided into obese group with cognitive impairment (MCI, n = 49) and obese cognitively normal group (Non_MCI, n = 55). In the erythrocyte membrane, the proportion of polyunsaturated fatty acids (PUFA), linoleic acid (C18:2 n-6) and arachidonic acid (C20:4 n-6) and n-6/n-3 ratio was higher in the MCI group than in the Non_MCI group. However, the α-linolenic acid (C18:3 n-3) percentage of the erythrocyte membrane was lower in the MCI group. We found that Coriobacteriales_Incertae_Sedis was positively correlated with erythrocyte membrane C20:4 n-6 and n-6 PUFA and negatively correlated with cognitive scores in obese patients. In addition, several of the functional pathways we predicted were significantly different in the MCI and Non_MCI groups. Higher levels of n-6/n-3 polyunsaturated fatty acids ratio in the erythrocyte membranes may influence the inflammatory response in the organism causing obesity induced cognitive damage. Moreover, high levels of n-6/n-3 polyunsaturated fatty acids ratio may also affect the intestinal flora of obese patients, which in turn may affect the cognitive function of obese patients.